2006
DOI: 10.1038/sj.onc.1209760
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitors induce the degradation of the t(8;21) fusion oncoprotein

Abstract: The t(8;21) chromosomal translocation that generates the fusion oncoprotein RUNX1-ETO predominates in leukemia patients of the French-American-British (FAB) class M2 subtype. The oncoprotein has the capacity to promote expansion of hematopoietic stem/progenitor cells and induces leukemia in association with other genetic alterations. Here, we show that RUNX1-ETO undergoes degradation in response to treatment with histone deacetylase inhibitors, one of which, depsipeptide (DEP), is currently undergoing phase II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 63 publications
6
53
0
Order By: Relevance
“…The Selectivity of low-dose ITF2357 in AML subtypes V Barbetti et al activity of z-VAD-fmk and Bortezomib was assessed in the same experiment (not shown). Heat shock protein 90 (Hsp90) is a chaperone protein known to stabilize AML1/ ETO (Yang et al, 2007). As evidenced in Figure 2f, ITF2357 0.1 mM did not induce Hsp90 acetylation, as already shown (Carta et al, 2006).…”
Section: Effects Of Itf2357 On Cell Number and Viabilitysupporting
confidence: 58%
“…The Selectivity of low-dose ITF2357 in AML subtypes V Barbetti et al activity of z-VAD-fmk and Bortezomib was assessed in the same experiment (not shown). Heat shock protein 90 (Hsp90) is a chaperone protein known to stabilize AML1/ ETO (Yang et al, 2007). As evidenced in Figure 2f, ITF2357 0.1 mM did not induce Hsp90 acetylation, as already shown (Carta et al, 2006).…”
Section: Effects Of Itf2357 On Cell Number and Viabilitysupporting
confidence: 58%
“…A better understanding of oncofusion proteins as mediators of epigenetically silenced states also drives the search for 'targeted' therapies that specifically antagonize their repressive effects. Examples for clinical models include treatment of PML/RARa transgenic mice with HDAC inhibitors, as well as AML1/ETOexpressing cell lines and transgenic cell models (Yang et al, 2007;Barbetti et al, 2008). Recently, the group of Clara Nervi has shown that the hypermethylated state of the RARb2 promoter CpG island can be converted to a demethylated, transcriptionally active promoter by treatment with the DNA-demethylating agent 5-azacytidine (Fazi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…28 Recently, the proteasomal degradation of AML1-ETO by FK228 was reported to result from the interrupted association of AML1-ETO with heat shock protein 90 (HSP90). 29 Adding to this understanding, our studies identified C/EBPa binding sites within the ANXA1 promoter region that contain no direct AML1-binding site. Our findings that FK228 upregulated the C/EBPa gene and promoted C/EBPa binding on the ANXA1 promoter indicate the possibility that C/EBPa-dependent ANXA1 transcriptional activation is one of the molecular mechanisms dictating the specificity of histone acetylation and transcriptional activation of the target genes in AML1-ETO-expressing AML cells.…”
Section: Discussionmentioning
confidence: 99%